Reasons for refusing antiretroviral therapy before completion of tuberculosis treatment at Pigg's Peak Hospital, Swaziland. - Phiri, Elias (University of Limpopo (Medunsa Campus), 2014)
Statistics from Pigg’s Peak Hospital, in Swaziland, continue to show an improvement in the uptake of HIV testing among TB patients, as well as a very high rate of HIV co-infection among the TB patients. The unit’s reports also show a low uptake of antiretroviral therapy among the HIV co-infected TB patients, and high death rates. Most of these deaths occur among HIV co-infected TB patients who have not yet initiated ART despite being on TB treatment. Anecdotal evidence suggests that there is reluctance and refusal by a considerable proportion of TB/HIV co-infected patients to take TB treatment and ART concurrently, and that they prefer to commence ART after completing TB treatment. No study has ever been conducted in Swaziland to determine the reasons for refusal of ART initiation prior to the completion of TB treatment among HIV co-infected TB patients. Aim The aim of this study was to explore the reasons for refusing antiretroviral therapy among HIV co-infected tuberculosis patients, prior to the completion of tuberculosis treatment, at Pigg’s Peak Hospital, in Swaziland. Methods A qualitative descriptive study was conducted in order to generate information on the subjects’ experiences and views on the concurrent taking of tuberculosis and antiretroviral medicines. A sample of nineteen HIV co-infected TB patients was purposefully selected to answer the research question. Results The most common reasons given by the respondents for refusing ART initiation during TB therapy were their un-readiness for ART, especially because ART must be taken for life, the perception that one was still in good health, the fear of adverse outcomes being precipitated by combining ART with TB medicines, a preference of traditional medicines, and health systems-related problems. Other reasons were: a lack of food, substance abuse, a fear of the increased pill burden, a denial of the HIV-positive status, and problems related to treatment supporters. Conclusion In TB/HIV co-infection care settings, comprehensive Pre-ART counseling must be integrated with interventions that address the specific barriers to ART initiation faced by clients; to improve the acceptability of ART initiation during TB therapy to these HIV/TB co-infected patients.
Thesis (MPH)--University of Limpopo, 2013.
Keywords: Antiretroviral therapy, highly active